Adscription to a Sui Iuris Church - Laschuk, Alexander M. (Studia canonica, 2020)
The proper determination of the ecclesial ascription of the Catholic faithful is necessary in ensuring the presence of the requisite jurisdiction which can be a factor impacting sacramental validity. The faithful are, in virtue of their baptism, incorporated into a specific Church. Membership in these Churches is governed by the norm of law and regulated by the Roman Pontiff in his capacity as supreme judge of relations between the Churches. The article first examines the canonical notion of the Church sui iuris and its conciliar and juridical foundations. The article then considers how one is incorporated into a specific Catholic Church and how that adscription can be transferred from one Church sui iuris to another.